Closing the loop: a campus-wide waste minimization initiative through education for sustainable development - Zen, Irina Safitri (Sejahtera Center for Sustainability & Humanity, 2021)
The food waste composting program reflect the circular economic practice at the Institution of higher Education by using IIUM as a case study. An action research of inter and trans-disciplinary of sustainability science covers the action research by Food waste composting groups which consist of practitioner and researcher. This effort supported by education for sustainable development, ESD approach to the campus community to stimulate more involvement of campus community through research, education and community engagement. Several achievements were documented.